The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/fonc.2020.569933
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Mortality in Young Women in Brazil

Abstract: ObjectiveMalignant breast cancer is the leading cause of death by cancer in young women. The study aimed to determine if breast cancer mortality among young women has increased between the period from 1996 to 2017 in Brazil.MethodsA time-series analysis of breast cancer mortality rate in young women (20–39 years old) was carried out. Mortality data, from 1996 to 2017, were collected from the Mortality Information System of the Health Ministry, and demographic data, from the Brazilian Institute of Geography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
(25 reference statements)
3
6
0
10
Order By: Relevance
“…Although the N0 women at a young age were more likely to have DM, compared with elderly women, the young population, however, had better long-term outcomes than the elderly population (HR= 1:1.58; 95% CI: 1.03-2.44). This result was consistent with one recent large population-based epidemiological study in Brazil that young women had a lower rate of modality (31).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although the N0 women at a young age were more likely to have DM, compared with elderly women, the young population, however, had better long-term outcomes than the elderly population (HR= 1:1.58; 95% CI: 1.03-2.44). This result was consistent with one recent large population-based epidemiological study in Brazil that young women had a lower rate of modality (31).…”
Section: Discussionsupporting
confidence: 93%
“…Although the N0 women at a young age were more likely to have DM, compared with elderly women, the young population, however, had better long-term outcomes than the elderly population (HR= 1:1.58; 95% CI: 1.03–2.44). This result was consistent with one recent large population-based epidemiological study in Brazil that young women had a lower rate of modality ( 31 ). On the contrary, in another study by Sabiani and colleagues, they concluded that patients at a young age (<35 years) had the lower estimated disease-free survival (DFS) and OS rate ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Nearly 40% of breast cancers occur in patients aged over 65 years and 25% in patients aged over 70 years. As the global population ages, the number of older patients with breast cancer will continue to increase ( 2 , 4 ). Therefore, breast cancer in the elderly will represent a major public health issue during the next decades.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, the number of new cancer cases worldwide exceeded 19 million, and nearly 10 million cancer deaths were reported . Furthermore, breast and colorectal cancers are among the cancers with the highest incidence and mortality. , In Brazil, breast and colorectal cancers follow world estimates, representing the first and second most common cancer type in women and men, respectively, except for nonmelanoma skin cancer. …”
mentioning
confidence: 99%